Interactive Storytelling for Fostering Adolescents’ Sustainability Mentalities - Design of a Physical Installation to Provoke Reflections About the Relationship Between Human, Nature and Consumption - Razocky, Abbas; Xie, Sofia (My University, 2025)
Amidst rising concerns about climate change and overconsumption, this thesis explores how interactive storytelling can support adolescents in reflecting on their consumption behaviors and discovering sustainable alternatives to possibly unsustainable behaviours. Drawing on theories of overconsumption, fundamental needs, and speculative design, the thesis investigates how abstract sustainability issues can be made tangible and personally relevant for young people. A mixed-methods user study involving 52 upper-secondary school students in Gothenburg revealed that adolescents primarily associate sustainability with personal wellbeing rather than environmental or societal dimensions. The study also highlighted a greater willingness to change behaviors that directly affect their health and lifestyle over those perceived as environmentally impactful. Based on these insights, an interactive storytelling installation, Vänskapsprövningen, was developed to symbolically represent the relationship between humanity, nature, and consumption. Through metaphor, multisensory elements, and participatory reflection, the installation aimed to bridge the gap between abstract sustainability narratives and everyday experiences. User evaluations demonstrated that the design fostered emotional engagement and self-reflection, suggesting that speculative and interactive storytelling can be effective tools for activating sustainable attitudes among adolescents. The thesis contributes to the field of design for sustainable behavior by proposing a replicable work for emotionally resonant behavior change interventions targeted at youth.